99mTc‐labeled Duramycin for detecting and monitoring cardiomyocyte death and assessing atorvastatin cardioprotection in acute myocardial infarction. (3rd September 2020) - Tan, Hui; Abudupataer, Mieradilijiang; Qiu, Lin; Mao, Wujian; Xiao, Jie; Cheng, Dengfeng; Shi, Hongcheng
Abstract: This study aimed to dynamically monitor myocardial cell death using 99m Tc‐Duramycin single‐photon emission computed tomography/computed tomography (micro‐SPECT/CT) imaging in acute myocardial infarction (AMI) and the anti‐apoptosis effect of atorvastatin for cardioprotection. Mice were randomized into three groups: AMI group, AMI with atorvastatin treatment (T‐AMI) group, and sham group. Three groups of model mice were randomly selected at day 1 (D1), day 3 (D3), and day 7 (D7) day after surgery with 99m Tc‐Duramycin micro‐SPECT/CT imaging. The lesion‐to‐normal myocardial tissue ratio (L/N) average values were 2.62 on D1, 3.89 on D3, and 1.20 on D7 for the uptake of 99m Tc‐duramycin in the infarcted region in the AMI group. The sham group presented no positive imaging in myocardium, and the L/N average values were 1.09, 1.14, and 1.10 on D1, D3, and D7, respectively. Meanwhile, 99m Tc‐linear‐duramycin imaging showed no radioactive uptake in the infarction region. The T‐AMI group imaging showed tracer uptake decreased obviously compared to the uptake in the infarcted region in AMI mice. 99m Tc‐Duramycin SPECT/CT imaging allowed non‐invasive monitoring of myocardial cell death in a mouse model of AMI and an assessment of atorvastatin anti‐apoptosis effect for cardioprotection by in vivo molecular imaging. Abstract : 99m Tc‐Duramycin single‐photon emission computed tomography/computed tomography imaging allowed for dynamically monitoring myocardial cell death in a mouse model of acute myocardial infarction. Furthermore, this probe could be used to assess and verify anti‐apoptotic effect of atorvastatin for cardioprotection by in vivo molecular imaging. This will provide powerful imaging guidance for in vivo evaluating new drugs for treating myocardial infarction in the future.